Risk factors for foot ulcers among patients with diabetes mellitus - MRS. A. MANJULA; DR.PRASANNABABY; DR.S.J.NALINI; DR.R.RAMYA (International Journal of Pharma and Bio Sciences, 2018)
This is a study to assess the diabetic foot ulcer risk factors among patients with diabetes mellitus at Sri Ramachandra Hospital, Porur, Chennai. Our aim is to identify diabetic foot ulcer risk factors and suggest ways to prevent, to identify the diabetic foot ulcer risk factors among patients with diabetes mellitus. The objective of the study is to associate the diabetic foot ulcer risk factors with selected background variables among patients with diabetes mellitus. The research design adopted for this study is descriptive in nature. The study was conducted in diabetic OPD of Sri Ramachandra hospital among 30 patients who satisfy the inclusion criteria. The instrument used consists of “Diabetic foot ulcer risk assessment form” developed by the registered Nurses Association of Ontario with 10 items that included history of foot ulcers, Protective sensation, Structural abnormalities, Circulation, Self care knowledge and behavior. All the 10 items are dichotomous with yes or no responses. Among the 30 patients, 10(33.3%) evince high risk for developing diabetic foot ulcer and 25(83.3%) suffer from knowledge deficit. Identifying complications and preventing at the earliest might be a boon for the patients. The nurse plays a pivotal role in educating the patients and helps them understand the disease and its management.